Open pronation abduction ankle fractures associated with increased complications and patient BMI. Issue 4 (April 2020) - Kahan, Joseph; Brand, Jordan; Schneble, Christopher; Li, Don; Saad, Maarouf; Kuether, Justin; Yoo, Brad
Highlights: Open pronation abduction ankle fractures are associated with increased patient BMI and increased number of reoperations. Abstract: Introduction: Pronation abduction (PA) ankle fractures are often associated with a medial tension failure wound. Though this injury pattern was defined based on the mechanism of injury, there is a paucity of literature evaluating risk factors for understanding which patients will sustain an open PA fracture. Furthermore, how patients with these types of fractures perform relative to other open ankle fractures has not been established. We hypothesized that open PA fractures are associated with obesity and increased number of reoperations. Methods: All patients at a single level one trauma center who received operative treatment for an ankle fracture between February 2012 to January 2019 were retrospectively identified using Current Procedural Terminology (CPT) codes. Patients with open PA ankle fractures were identified. Demographic data, body mass index, medical comorbidities, time to surgery, and reoperations were compared between open PA ankle fractures and other open ankle fracture subtypes. Results: There were 22 open PA ankle fractures and 35 other open ankle fracture subtypes. The open PA fracture group had a significantly higher median and average BMI and percentage of patients with obesity. There was no difference in number of patients requiring reoperation between the two groups. When reoperation was required, patients with open PA ankle fractures were found to undergo significantly more reoperations and were significantly more likely to require arthrodesis or below knee amputation. Conclusions: Open PA ankle fractures are more often associated with obesity (BMI > 30 kg/m 2 ) than are other open ankle fractures caused by a different mechanism. When reoperation does occur, patients with open PA ankle fractures require more reoperations and are more likely to require arthrodesis or below knee amputation that patients with other open ankle fracture subtypes. Early identification of those patients or injuries at increased risk of complications can help ensure optimal outcomes.